7 ensayos, la teoría de la praxis en América, 90 años después: la cuestión indígena y el problema de la tierra (Revista de Crítica Literaria Latinoamericana, 2019)
I propose a reading of Mariátegui’s 7 essays considering the importance that he gives to the indigenous cultural factor as part of the revolutionary struggle in Peru. I also explain the construction of socialism as a development of state capitalism and the reason why socialism in China is sustained on the basis of peasant power.
Keywords: Mariátegui; Peru; socialism; indigenous culture; Chinese peasantry